Phylogeographic analysis reveals extensive genetic variation of native grass Elymus nutans (Poaceae) on the Qinghai-Tibetan plateau - Li, Jin; Li, Xinda; Zhang, Changbing; Zhou, Qingping; Chen, Shiyong (Frontiers in Plant Science, 2024)
Introduction Elymus nutans holds ecological and pastoral significance due to its adaptability and nutritional value, the Qinghai-Tibet Plateau (QTP) is a key hub for its genetic diversity. To conserve and harness its genetic resources in highland ecosystems, a thorough assessment is vital. However, a comprehensive phylogeographic exploration of E. nutans is lacking. The objective of this study was to unravel the genetic diversity, adaptation, and phylogenetics of E. nutans populations. Methods Encompassing 361 individuals across 35 populations, the species' genetic landscape and dynamic responses to diverse environments were decoded by using four chloroplast DNA (cpDNA) sequences and nine microsatellite markers derived from the transcriptome. Results and discussion This study unveiled a notable degree of genetic diversity in E. nutans populations at nuclear (I = 0.46, He = 0.32) and plastid DNA levels (Hd = 0.805, π = 0.67). Analysis via AMOVA highlighted genetic variation predominantly within populations. Despite limited isolation by distance (IBD), the Mekong-Salween Divide (MSD) emerged as a significant factor influencing genetic differentiation and conserving diversity. Furthermore, correlations were established between external environmental factors and effective alleles of three EST-SSRs (EN5, EN57 and EN80), potentially linked to glutathione S-transferases T1 or hypothetical proteins, affecting adaptation. This study deepens the understanding of the intricate relationship between genetic diversity, adaptation, and environmental factors within E. nutans populations on the QTP. The findings shed light on the species' evolutionary responses to diverse ecological conditions and contribute to a broader comprehension of plant adaptation mechanisms.